2022
DOI: 10.1155/2022/8351868
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Digital Construction of Vocal Music Teaching Resource Base Using Data Mining Technology

Abstract: Vocal music teaching resource databases can support teachers’ instruction and students’ learning while also enhancing the school’s ability to run a school because they are the main components of digital construction for vocal music teaching. Currently, system application is the main area of research for DM (data mining), which was previously focused on method discovery. A vocal music teaching resource base based on DM technology is created by using the theme as the central organising principle, processing, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Xu, N processed and organized the resources to construct a vocal music resource base based on data mining technology. Thematic resource development is used to integrate lesson preparation, teaching, self-study, and output resources into the digital information network resource application environment [14]. Ding, J develops a vocal music teaching system with a computer-aided teaching function and extracts the performance characteristics of vocal music by using the Fourier transform and its improvement function [15].…”
Section: Introductionmentioning
confidence: 99%
“…Xu, N processed and organized the resources to construct a vocal music resource base based on data mining technology. Thematic resource development is used to integrate lesson preparation, teaching, self-study, and output resources into the digital information network resource application environment [14]. Ding, J develops a vocal music teaching system with a computer-aided teaching function and extracts the performance characteristics of vocal music by using the Fourier transform and its improvement function [15].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%